Long-term evolution of the stratification, winter mixing and θ-S signature of upper water masses in the southeastern Bay of Biscay. (15th June 2019) - Valencia, Víctor; Fontán, Almudena; Goikoetxea, Nerea; Chifflet, Marina; González, Manuel; López, Ander
Abstract: More than three decades (1986–2017) of hydrographic measurements from nearly monthly ship-based CTDs have been complemented with high-frequency hydrographic measurements from a moored deep-sea buoy in the southeastern Bay of Biscay. The analysis of hydrographic data led to the estimation of the temporal evolution of the stratification and winter mixing and the potential temperature and salinity signatures of the winter mode upper waters. Comparison of the acquisition techniques (autonomous versus ship-based) shows that hydrographic datasets should be used as complementary data rather than individually. The results obtained reveal that the thermocline has deepened from 2007 and the most intense winter mixing event occurred in 2005, followed by the episode of winter 2009. Finally, the strongest warming and salinification of the Eastern North Atlantic Central Water took place in 1991 due to the persistence of mild and dry winters and decreased winter mixing over the preceding years. Highlights: Ship-based and autonomous hydrographic measurements are complementary acquisition techniques. The thermocline depth has deepened from 2007 in the SE Bay of Biscay. The most intense winter mixing event occurred in 2005 in the SE Bay of Biscay. The strongest warming and salinification of the ENACW took place in 1991 in the area.